Horsetail (Equisetum, Equisetaceae) in commerce and exported from Peru - León, Blanca (2012)
Several plant products are exported from Peru as food supplements (nutraceuticals), condiments and other uses for human consumption, among them the horsetail fern. Three names are used in commerce: Equisetum arvense, E. bogotenseand “E. hiemale”; none of which represent the species being exported; instead the spe-cies in commerce is E. giganteum, easily recognizable by morphological details of their axes, ornamentation and stomata distribution.